PENERAPAN MAJORITY VOTE METHOD DALAM PENENTUAN PEMBOBOTAN PADA METODE WEIGHTED PRODUCT (WP) PADA PEMERINGKATAN KAMPUS DI KOTA MEDAN - Adidtya Perdana; Nurul Ain Farhana (Deli Sains Informatika, 2022)
There are many campuses in the city of Medan that can be used as a place for anyone to study. But not all campuses have good quality and ranking. For this reason, it is necessary to know which campuses have the best rankings. In this article, it is a publication of ongoing research that the author has conducted on the ranking of campuses or colleges in the city of Medan by applying methods to the Decision Support System. And in this article, the author makes a slight modification using the Majority Vote method which is part of the Bagging in the Random Forest Classification at the stage of determining weighting with the main method being Weighted Product (WP). The purpose of this modification is to see the results displayed in determining whether the campus ranking gives optimal results or not. After the analysis and calculations were carried out, the result was that modifying the weighting process using the Majority Vote could provide optimal and varied results in solving the problem of ranking campuses in the city of Medan. And in the future, modifications can use other methods or equations and compare the results given.